Planejamento da expansão de sistemas elétricos de distribuição considerando a tarifação da transmissão e aspectos de confiabilidade - Santos, Moises Machado (2017)
The main premise for the countries that have adopted the competition model to generation and energy market is the decentralization of activities of the generation, transmission and distribution of energy. In this structure, the investments in expansion of generation, transmission and distribution systems is performed by distinct agents. On this regard, the proper allocation of network costs through locational pricing is essential to the development of electricity sector agents. The main goal of applying locational use of system tariffs is providing an appropriate remuneration of transmission system companies. The definition of this tariffs takes into consideration the “extension of the use” of each user based on its location. Among many attributes, such tariffs promote a more rational use of transmission assets as well as the reduction of operational costs. However, the locational signal price from Transmission Network Use of System (TNUoS) is not yet systematically explored in the distribution system planning context. Regarding that, this thesis presents the development of a model for distribution system expansion planning that includes the transmission tariffs. It is proposed the minimization of costs of use of transmission system, investments, operation and Expected Energy Not Supplied (EENS). The expansion alternatives consist of: installation and repowering of substations; allocation of switching devices; and the construction of interconnection circuits between feeders. The allocation of switching devices and construction of interconnection circuits aim at providing more flexibility to the operation in order to mitigate the impacts of outages in the network. The model is formulated as a Mixed Integer Nonlinear Program (MINLP) and the metaheuristic GRASP (Greedy Randomized Adaptive Search Procedure) is adopted as solution algorithm. The methodology is developed in AMPL (A Modeling Language for Mathematical Programming) and the solver (Nonlinear Interior-point Trust Region Optimizer) is used as optimization tool. The validation tests are performed using IEEE System Tests of 23, 54 and 182 buses. The results demonstrate the potentials of the proposed methodology, which obtained reduction in expansion costs. In addition, the developed methodology provide subsidies to the distribution companies, allowing to establish agreements to use the transmission system.